Determinants of biodiversity in subtropical shallow lakes (Atlantic coast, Uruguay) - Kruk, Carla (2009)
SUMMARY 1. Shallow lakes and ponds contribute disproportionally to species richness relative to other aquatic ecosystems. In-lake conditions (e.g. presence of submerged plants) seem to play a key role in determining diversity, as has been demonstrated for temperate lakes. When water quality deteriorates and turbidity increases, conditions in such lakes are affected drastically resulting in a loss of diversity. However, it is not clear whether subtropical lakes show the same pattern and whether the richness of all groups reacts similarly to environmental changes. 2. Our aim was to analyse the main factors explaining patterns of species richness in plankton, fish and submerged macrophyte assemblages in both turbid and clear subtropical shallow lakes. We analysed abiotic and biotic features of 18 subtropical, small- to mediumsized, shallow lakes along the Uruguayan coast. We compared both turbid and clear ecosystem states and evaluated the relative variance explained by the factors measured. 3. Variables describing lake and catchment morphology, as well as the percentage of the water column occupied by submerged macrophytes (%PVI) and water turbidity, had strong effects on taxon richness. Interestingly, individual biotic groups had dissimilar richness patterns. Macrophyte %PVI decreased with increasing lake area, while fish species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. strong effects on taxon richness. Interestingly, individual biotic groups had dissimilar richness patterns. Macrophyte %PVI decreased with increasing lake area, while fish species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. strong effects on taxon richness. Interestingly, individual biotic groups had dissimilar richness patterns. Macrophyte %PVI decreased with increasing lake area, while fish species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. %PVI) and water turbidity, had strong effects on taxon richness. Interestingly, individual biotic groups had dissimilar richness patterns. Macrophyte %PVI decreased with increasing lake area, while fish species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. %PVI decreased with increasing lake area, while fish species richness showed the opposite pattern. Phytoplankton species richness increased with macrophyte %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes. %PVI, while the zooplankton richness pattern varied depending on the taxonomic group considered. 4. Overall, our results indicate that, as found for temperate lakes, a greater submerged plant cover promotes higher species richness in several groups, and that this may overwhelm the otherwise expected positive effect of lake size on species richness. On the other hand, small-bodied zooplankton predominated in lakes with high plant abundance. Our findings concur with recent studies, indicating that refuge capacity of aquatic plants might be weaker in (sub)tropical than in temperate shallow lakes.